MOTORCYCLE RIDER BEHAVIOUR OF TARUMANAGARA UNIVERSITY LECTURER AND EMPLOYEE - Putranto, Leksmono Suryo; Setyarini, Ni Luh Putu Shinta Eka; Rostiana, Rostiana; Bunawan, Rudy (FSTPT Indonesia, 2015)
In Indonesian cities, usually a car owner also own a motorcycle to avoid congestion. This cause many problem such as unskilled rider, traffic violation, aggressive behaviour etc. Instruments to assess motorcycle rider behaviour were developed in England, Iran, Turkey, China and Australia. Putranto and Anjaya (2014) propose Indonesian Motorcycle Rider Behaviour Questionnaire (MRBQ) as MRBQ was prove to be sensitive to local culture and social system. This paper is further development of Indonesian MRBQ. Previously the instrument was prepared without strong theoritical basis. In this present paper the instrument was adjustment of Persian MRBQ. After an FGD with experts in motorcycle rider behaviour only 42 items from 48 items in Persian MRBQ were used in in this study. All valid and reliable items were anlysed to compare wheter there are different behaviour between different gender, age, whealth level, job, ethnicity, etc. Respondents were lecturers and employees of Tarumanagara University.